Islamic Banking, Credit and Economic Growth: Some Empirical Evidence - Guglielmo Maria Caporale; Mohamad Husam Helmi (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper examines the effects of Islamic banking on the causal linkages between credit and GDP by comparing two sets of seven emerging countries, the first without Islamic banks, and the second with a dual banking system including both Islamic and conventional banks. Unlike previous studies, it checks the robustness of the results by applying both time series and panel methods; moreover, it tests for both long- and short-run causality. In brief, the findings highlight significant differences between the two sets of countries reflecting the distinctive features of Islamic banks. Specifically, the time series analysis provides evidence of long-run causality running from credit to GDP in countries with Islamic banks only. This is confirmed by the panel causality tests, although in this case short-run causality in countries without Islamic banks is also found.
Keywords: C32; C33; G21; O11; 330; credit; growth; Islamic banking causality tests